A multi-gradient proportioning test determines a coal slime replacement tail coal matching method

CN122958081APending Publication Date: 2026-10-23AKESU TIANSHAN DUOLANG CEMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610965118.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-30
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0008]为了解决现有煤泥替代尾煤配料方法中缺乏系统性配伍试验流程、替代比例确定盲目以及评价指标单一割裂的问题,本申请设计了一种多梯度配比试验确定煤泥替代尾煤配伍方法,该方法通过设计多组煤泥对尾煤替代率呈梯度递增的配比方案,依次进行原料化学成分基准确定、生料易磨性试验和生料易烧性试验,获得不同替代率方案下的易磨性指数序列数据和指定煅烧温度下的游离氧化钙含量值,进而建立以煤泥对尾煤替代率为自变量、以易磨性指数和指定煅烧温度下游离氧化钙含量为因变量的数据联动关系,并基于粉磨能耗经济性约束条件和熟料质量约束条件确定最优替代率窗口,在最优替代率窗口内最终确定煤泥替代尾煤的最佳配伍比例,以实现兼顾粉磨能耗、熟料质量和煤泥消纳量的科学精准配料,为煤泥在水泥生料中的大规模资源化利用提供一种标准化、可复制的试验确定方法

Benefits of technology

[0031]一、本发明通过设计多组呈梯度递增的煤泥对尾煤替代率的配比方案,依次进行原料化学成分基准确定、生料易磨性试验和生料易烧性试验,构建了一条从成分配比到粉磨特性再到煅烧性能的完整递进式试验链条,本申请将不同煤泥替代率方案下的易磨性指数序列数据与指定煅烧温度下游离氧化钙含量值进行联动分析,建立了煤泥替代率与粉磨性能、烧成性能之间的数据联动关系,这种联动评价机制使得每一个替代率方案的工艺适配性都能从粉磨能耗和熟料质量两个维度同时被审视,确保了最终确定的配伍方案在全生产流程中均具有优益的工艺适应性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958081A_ABST
    Figure CN122958081A_ABST
Patent Text Reader

Abstract

The application discloses a kind of multi-gradient proportioning test determination slime replacement tail coal compatibility method, it is related to solid waste resource utilization technical field, by designing multiple groups of coal slime to tail coal replacement rate gradient increasing proportioning scheme, in turn, raw material chemical composition benchmark determination, raw material grindability test and raw material burnability test are carried out, obtain the grindability index sequence data under different replacement rate scheme and the free calcium oxide content value under specified calcination temperature, and then establish the data linkage relationship with coal slime to tail coal replacement rate as independent variable, with grindability index and the free calcium oxide content under specified calcination temperature as dependent variable, and determine optimal replacement rate window based on grinding energy consumption economy constraint condition and clinker quality constraint condition, finally determine the best compatibility ratio of slime replacement tail coal in optimal replacement rate window, to realize grinding energy consumption, clinker quality and slime accommodation amount scientific and accurate proportioning.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid waste resource utilization technology, specifically a method for determining the compatibility of coal slime as a substitute for tailings coal through multi-gradient proportioning experiments. Background Technology

[0002] In the cement production process, raw material batching is the core link that determines clinker quality and production cost. In traditional batching schemes, tailings, namely low-calorific-value coal gangue or coal waste after washing, are used as a calorific-value silicon-aluminum corrective raw material. The purpose is to utilize the small amount of residual calorific value in the tailings to reduce the heat consumption of clinker burning, while providing the necessary silicon and aluminum oxide components.

[0003] Coal slime is a byproduct of coal washing and processing. It is characterized by high moisture content, high ash content, low calorific value, and high viscosity. Compared with tailings, coal slime has significant differences in chemical composition, mineral composition, and combustion characteristics. Currently, the stockpiling of large amounts of coal slime not only occupies land resources but also causes serious environmental pollution. Using coal slime as an alternative raw material in cement raw material batching is a reliable way to achieve its large-scale, harmless, and resource-based utilization.

[0004] However, most existing methods for replacing tailings with coal slime are based on experience or simple substitution of single chemical components, which have the following significant drawbacks:

[0005] The lack of systematic compatibility testing methods means that existing technologies do not incorporate multi-dimensional performance indicators such as chemical composition analysis, raw material grindability, and raw material burnability into a unified and progressive testing system, making it impossible to comprehensively evaluate the impact of coal slime replacing tailings on the performance of the entire cement production process.

[0006] The determination of the replacement ratio is arbitrary, relying solely on equal replacement based on heat and oxide content. It fails to accurately grasp the dynamic impact of different coal slime replacement ratios on the grinding and calcination characteristics of raw materials, resulting in large fluctuations in raw material quality and unstable kiln conditions after replacement.

[0007] Therefore, there is an urgent need to develop a comprehensive and systematic experimental method to accurately determine the optimal ratio of coal slime to tailings. Summary of the Invention

[0008] To address the shortcomings of existing methods for replacing tailings with coal slime, such as the lack of systematic compatibility testing procedures, the blind determination of replacement ratios, and the fragmented nature of evaluation indicators, this application proposes a multi-gradient ratio testing method for determining the compatibility of coal slime with tailings. This method designs multiple ratio schemes with progressively increasing coal slime replacement rates, sequentially determining the raw material chemical composition baseline, conducting raw meal grindability tests, and raw meal burnability tests. This yields grindability index sequence data and free calcium oxide content values ​​at specified calcination temperatures under different replacement rate schemes. Furthermore, it establishes a data linkage relationship with the coal slime replacement rate as the independent variable and the grindability index and free calcium oxide content at the specified calcination temperature as dependent variables. Based on constraints related to grinding energy consumption and clinker quality, an optimal replacement rate window is determined. Within this window, the optimal ratio of coal slime to tailings is finally determined, achieving scientific and precise batching that balances grinding energy consumption, clinker quality, and coal slime consumption. This provides a standardized and replicable experimental method for the large-scale resource utilization of coal slime in cement raw materials.

[0009] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a method for determining the compatibility of coal slime as a substitute for tailings coal through multi-gradient proportioning tests, the specific steps of which are as follows:

[0010] S100. Perform chemical composition analysis on the target coal slime sample and the reference tailings sample respectively, determine the main oxide content, moisture and received lower heating value of the target coal slime sample and the reference tailings sample respectively, and establish a basic chemical composition database of the target coal slime and a basic chemical composition database of the reference tailings.

[0011] S200. Design N groups of multi-gradient proportioning schemes for replacing tailings with coal slime, including multiple experimental group schemes and blank control group schemes. By adjusting the amount of limestone, sandstone and iron powder raw materials, keep the target rate values ​​of lime saturation coefficient, silicon content and aluminum content of raw materials in the blank control group scheme and all experimental group schemes consistent with the target rate values ​​of the benchmark raw material proportioning scheme.

[0012] S300. According to the blank control group scheme and all test group schemes, weigh, mix and grind the various raw materials required for each scheme according to the ratio to prepare N groups of raw material samples corresponding to the number of schemes. Perform grindability test on each of the N groups of raw material samples, record the unit energy consumption required to grind each group of raw material samples to the preset surface area, calculate the grindability index corresponding to each group of raw material samples, and obtain grindability index sequence data composed of N grindability indices.

[0013] S400. Take N groups of raw material samples prepared in step S300 respectively. Under the same working conditions, place each group of raw material samples at three different calcination temperatures for isothermal calcination tests. After calcination, quickly cool to obtain clinker samples corresponding to each group of raw material samples at each calcination temperature. Measure the free calcium oxide content of each clinker sample one by one to obtain the free calcium oxide content value corresponding to each group of raw material samples at the specified calcination temperature and use it as a burnability characteristic parameter. The burnability characteristic parameter includes at least the free calcium oxide content value at the specified calcination temperature.

[0014] S500. Using the coal slime replacement rate for tailings determined in step S200 as the independent variable, and the grindability index obtained in step S300 and the clinker free calcium oxide content at the specified calcination temperature obtained in step S400 as the dependent variables, a data linkage relationship is constructed between the coal slime replacement rate and the grindability index and the clinker free calcium oxide content at the specified calcination temperature, respectively. Based on the data linkage relationship, according to the upper limit critical value of the grindability index preset for cement production, and the upper limit critical value of the free calcium oxide content that ensures the quality of clinker, the range of coal slime replacement rates for tailings that simultaneously satisfy the upper limit critical value of the grindability index and the upper limit critical value of the free calcium oxide content is determined.

[0015] S600. The range of coal slime to tailings replacement rate is taken as the optimal replacement rate window. Within the range of the optimal replacement rate window, the optimal ratio of coal slime to tailings is finally determined by combining the stability of coal slime supply and the economic factors of batching.

[0016] Furthermore, in the N groups of multi-gradient ratio schemes for replacing tailings with coal slime, the first group scheme is a blank control group scheme with a coal slime replacement rate of 0 wt.% for tailings, and the second group scheme to the Nth group scheme are experimental group schemes. The coal slime replacement rate for tailings in the second group scheme to the Nth group scheme increases in a gradient of mass percentage until the coal slime replacement rate for tailings in the Nth group scheme reaches 100 wt.%.

[0017] Furthermore, in S300, the grindability test is conducted using the Bond work index method. The grindability index is defined as the grinding work index corresponding to the specific surface area of ​​each group of raw material samples reaching 320±10m2 / kg. ,in, The grindability index, i.e., energy consumption per unit, This refers to the sieve aperture size that allows 80% of the ground product to pass through. The sieve aperture size is the size at which 80% of the feed material passes through the mill. To test the amount of newly produced fine powder per revolution of the mill, the grinding work index was determined. The smaller the value, the better the grindability of the raw material samples, and the better the grinding economy of the corresponding coal slime in terms of tailings replacement rate.

[0018] Furthermore, in S400, there are three different calcination temperatures: 1350℃, 1400℃, and 1450℃. The specified calcination temperature is 1400℃. The free calcium oxide content of the clinker measured at the calcination temperature of 1400℃ is used as the characteristic parameter of calcinability, and the data linkage analysis in S500 is performed.

[0019] Furthermore, the specific steps of S500 are as follows:

[0020] The core evaluation indicators were determined, including the qualified rate of loss on ignition of clinker after calcination of each group of raw meal samples, the grindability index, and the free calcium oxide content of clinker at a specified calcination temperature.

[0021] The core evaluation indicators were subjected to dimensionless normalization, and the original values ​​of each core evaluation indicator were uniformly mapped to dimensionless values ​​in the range of [0, 1]. For the grindability index and free calcium oxide content, the closer the dimensionless value is to 1, the better the performance, and the closer it is to 0, the worse the performance.

[0022] Based on the importance of the core evaluation indicators to the overall benefits of cement raw meal preparation and clinker calcination, weighting coefficients are assigned to the loss on ignition qualification rate, grindability index, and free calcium oxide content, respectively. , , γ, and satisfy ;

[0023] according to Calculate the overall fitness score for each formulation. ,in, For the first The overall fitness score of the formulation scheme. , For the first The normalized value of the qualified rate of loss on ignition in the formulation scheme. For the first The normalized value of the grindability index of the formulation scheme. For the first The normalized value of the free calcium oxide content under the specified calcination temperature in the formulation scheme;

[0024] Comprehensive fitness score The coal slime replacement rate of tailings corresponding to the highest value is taken as the optimal compatibility center. A comprehensive fitness score is formed by expanding outwards from the optimal compatibility center. A continuous substitution rate range that is not lower than a preset threshold is used as the optimal substitution rate window.

[0025] Furthermore, in S200, the lime saturation coefficient value The allowable deviation range is ±0.01, silicon ratio value The allowable deviation range is ±0.05, aluminum ratio value The permissible deviation range is ±0.05;

[0026] The lime saturation coefficient value The silicon ratio value The aluminum ratio value Among them, CaO, , , These represent the mass percentage of the corresponding oxides in the raw meal.

[0027] Furthermore, in S100, the main oxide contents determined by chemical composition analysis of the target coal slime sample and the reference tailings sample include the mass percentages of loss on ignition, silicon dioxide, aluminum oxide, ferric oxide, calcium oxide, and magnesium oxide.

[0028] Furthermore, in the isothermal calcination test of the S400, the isothermal calcination time at each calcination temperature is 30-60 minutes, and the rapid cooling adopts air cooling or water cooling to cool the calcined clinker sample from the calcination temperature to <100°C within 5 minutes.

[0029] Furthermore, in S600, the center value of the optimal substitution rate window is taken as the determined optimal blending ratio of coal slime to tailings.

[0030] Compared with existing technologies, this multi-gradient proportioning test method for replacing tailings coal has the following advantages:

[0031] I. This invention designs multiple gradient-increasing coal slime-to-tail coal replacement ratio schemes, sequentially determining the raw material chemical composition benchmark, raw meal grindability test, and raw meal burnability test, constructing a complete progressive test chain from component ratio to grinding characteristics to calcination performance. This application performs linkage analysis on the grindability index sequence data under different coal slime replacement ratio schemes and the free calcium oxide content value under a specified calcination temperature, establishing a data linkage relationship between coal slime replacement rate and grinding performance and calcination performance. This linkage evaluation mechanism allows the process adaptability of each replacement ratio scheme to be examined simultaneously from two dimensions: grinding energy consumption and clinker quality, ensuring that the finally determined compatibility scheme has excellent process adaptability throughout the entire production process.

[0032] Second, this invention uses the coal slime substitution rate for tailings as the independent variable and the grindability index and the free calcium oxide content in clinker at a specified calcination temperature as the dependent variables. It constructs a data linkage relationship between the coal slime substitution rate and the grindability index and the free calcium oxide content in clinker at a specified calcination temperature, respectively. Based on the upper limit critical value of the grindability index that allows for economic efficiency in grinding and the upper limit critical value of the free calcium oxide content that ensures clinker quality, it accurately defines the optimal substitution rate window that simultaneously satisfies both constraints. This transforms the process constraints into quantifiable and determinable numerical boundaries, enabling the selection of the substitution ratio to shift from empirical trial and error to data-driven window positioning.

[0033] Other advantages, objectives and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination or study, or may be learned from the practice of the invention. Attached Figure Description

[0034] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without any creative effort.

[0035] Figure 1 This is a flowchart illustrating the steps of a multi-gradient proportioning test to determine the compatibility of coal slime as a substitute for tailings in an embodiment of the present invention.

[0036] Figure 2 This is a flowchart illustrating the use of a weighted comprehensive scoring method to determine the optimal substitution rate window in an embodiment of the present invention. Detailed Implementation

[0037] To better understand the above technical solutions, a detailed description of the solutions will be provided below in conjunction with the accompanying drawings and specific embodiments. Obviously, the described embodiments are merely some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0038] In the description of this invention, the various raw material ratios, temperature parameters, time parameters, etc., involved are all specific examples of achieving the purpose of this invention. After reading this application document, those skilled in the art can make adaptive adjustments without departing from the concept of this invention. These adjustments all fall within the protection scope of this invention. In the embodiments of this invention, "coal slime" refers to the by-product with high moisture, high ash content, and low calorific value produced during the coal washing and processing process. "Tail coal" refers to the washed low-calorific-value coal gangue or coal waste used in the raw material batching in cement production.

[0039] This invention provides a method for determining the compatibility of coal slime as a substitute for tailings through multi-gradient proportioning tests, such as... Figure 1 As shown, the steps of this method are as follows:

[0040] S100. Perform chemical composition analysis on the target coal slime sample and the reference tailings sample respectively, determine the main oxide content, moisture and received lower heating value of the target coal slime sample and the reference tailings sample respectively, and establish a basic chemical composition database of the target coal slime and a basic chemical composition database of the reference tailings.

[0041] S200. Design N groups of multi-gradient proportioning schemes for replacing tailings with coal slime, including multiple experimental group schemes and blank control group schemes. By adjusting the amount of limestone, sandstone and iron powder raw materials, keep the target rate values ​​of lime saturation coefficient, silicon content and aluminum content of raw materials in the blank control group scheme and all experimental group schemes consistent with the target rate values ​​of the benchmark raw material proportioning scheme.

[0042] S300. Prepare N groups of raw material samples corresponding to the number of samples in the scheme. Perform a grindability test on each of the N groups of raw material samples, record the unit energy consumption required to grind each group of raw material samples to a preset surface area, calculate the grindability index corresponding to each group of raw material samples, and obtain a grindability index sequence data composed of N grindability indices.

[0043] S400. Take raw material samples and, under the same working conditions, place each group of raw material samples at three different calcination temperatures for constant temperature calcination tests. Obtain the clinker samples corresponding to each group of raw material samples at each calcination temperature. Measure the free calcium oxide content of each clinker sample one by one and obtain the free calcium oxide content value corresponding to each group of raw material samples at the specified calcination temperature as a characteristic parameter of calcinability.

[0044] S500: Construct the data linkage relationship between the coal slime replacement rate and the grindability index and the free calcium oxide content of clinker at a specified calcination temperature. Based on the upper limit critical value of the grindability index preset for cement production and the upper limit critical value of the free calcium oxide content allowed to ensure clinker quality, determine the range of coal slime replacement rate for tailings that simultaneously meets the upper limit critical value of the grindability index and the upper limit critical value of the free calcium oxide content.

[0045] S600. The range of coal slime to tailings replacement rate is taken as the optimal replacement rate window. Within the range of the optimal replacement rate window, an optimal ratio of coal slime to tailings is determined.

[0046] This method solves the problem of determining the optimal blending ratio when coal slime replaces tailings by constructing a progressive experimental chain that couples chemical composition analysis, raw material grindability, raw material burnability, and comprehensive benefit evaluation.

[0047] In a preferred embodiment, the method was verified in a laboratory and pilot plant of a cement plant. The coal slime used in the test was taken from the filter press product of a coal preparation plant near the plant, the reference tailings were taken from the plant's existing batching station, and the limestone, sandstone and iron powder used in the test were all raw materials currently used in the plant's production.

[0048] First, chemical composition analysis was performed on the target coal slime sample and the reference tailings sample to establish a basic chemical composition database. The target coal slime sample was sampled and placed in a forced-air drying oven to dry to constant weight at 105±5℃. Then, it was pulverized using a sealed sample preparation pulverizer so that all the pulverized sample passed through a square hole sieve with a pore size of 0.2mm to obtain the coal slime sample for analysis. The moisture, ash and volatile matter of the sample were determined, and the lower heating value of the sample on the received basis was determined using an oxygen bomb calorimeter.

[0049] Chemical composition analysis of coal slime samples was performed using X-ray fluorescence spectrometry to determine the mass percentage of major oxides in the samples, specifically including loss on ignition (LOI) and silica. Aluminum oxide ferric oxide Calcium oxide and magnesium oxide To ensure data accuracy, each sample was measured twice in parallel, and the arithmetic mean of the two measurements was taken as the final result.

[0050] The same pretreatment and testing procedures were applied to the benchmark tailings sample to obtain industrial analysis data, calorific value data, and content data of major oxides for the benchmark tailings sample.

[0051] In this embodiment, the chemical composition analysis results of the target coal slime sample and the reference tailings sample are shown in Table 1:

[0052]

[0053] All measurement data were entered into the database management system to establish a database of the basic chemical composition of the target coal slime and a database of the basic chemical composition of the benchmark tailings.

[0054] After establishing the basic chemical composition database, we designed a multi-gradient ratio scheme. Under the premise of keeping the key raw material ratio constant, we designed multiple experimental schemes in which the replacement rate of coal slime to tailings coal increases in a gradient.

[0055] A baseline raw meal proportioning scheme was determined. This scheme is the one currently used in cement plant production and can reliably produce qualified clinker. In the baseline raw meal proportioning scheme, the dry basis mass ratio of limestone, sandstone, iron powder, and tailings is: limestone 78.5%, sandstone 12.0%, iron powder 3.5%, and tailings 6.0%. Based on this ratio and the chemical composition data of each raw material, the theoretical yield value of the baseline raw meal was calculated, where the lime saturation coefficient is... Silicon ratio Aluminum ratio In the formula, CaO represents the mass percentage of calcium oxide in the raw meal. This represents the mass percentage of silica in the raw material. This represents the mass percentage of aluminum oxide in the raw meal. The mass percentage of ferric oxide in the raw meal is represented. In this embodiment, the theoretical rate values ​​of the reference raw meal are: lime saturation coefficient equal to 0.910, silicon ratio equal to 2.45, and aluminum ratio equal to 1.48. The lime saturation coefficient of 0.910, silicon ratio of 2.45, and aluminum ratio of 1.48 are used as the target rate values ​​for all proportioning schemes in this embodiment.

[0056] In this embodiment, 11 schemes were designed, with the first group being a blank control group scheme, where the replacement rate of coal slime with tailings was 0 wt.%. In this group, the amount of coal slime was 0, the amount of tailings was the same as the tailings mass in the baseline scheme, and the amounts of limestone, sandstone, and iron powder were recalculated to ensure that the final raw meal's lime saturation coefficient, silicon content, and aluminum content were exactly equal to the target values.

[0057] Groups 2 through 11 were experimental schemes, with the replacement rate of coal slime with tailings increasing in increments of 10 percentage points. That is, the replacement rates of Groups 2 through 11 were 10 wt.%, 20 wt.%, 30 wt.%, 40 wt.%, 50 wt.%, 60 wt.%, 70 wt.%, 80 wt.%, 90 wt.%, and 100 wt.%, respectively.

[0058] After determining the amount of coal slime and tailings for each scheme, the amounts of limestone, sandstone, and iron powder are adjusted to achieve the target raw meal ratio. In this embodiment, based on the chemical composition of the four raw materials—limestone, sandstone, iron powder, and calorific value-containing raw materials—a linear equation system containing three ratio equations and one total equation is established. The ratio of each raw material that meets the target ratio is solved by iterative method. Specifically, the target cells are set as the calculation cells for the lime saturation coefficient, silicon ratio, and aluminum ratio, so that they are equal to 0.910, 2.45, and 1.48, respectively. The variable cells are set as the ratios of limestone, sandstone, and iron powder, and non-negative constraints are set for each ratio to obtain the accurate ratios under each scheme.

[0059] During the calculation process, the allowable deviation of the lime saturation coefficient value is controlled within ±0.01, the allowable deviation of the silicon ratio value is controlled within ±0.05, and the allowable deviation of the aluminum ratio value is controlled within ±0.05. The final proportion data of all schemes are recorded and organized to form a scheme proportion table.

[0060] After completing the design of the proportioning scheme, raw material samples were prepared and grindability tests were conducted. The ease of grinding of raw materials with different proportioning schemes was quantified by using the standardized Bonder's index test.

[0061] According to the proportions of each scheme, limestone, sandstone, iron powder, tailings, and coal slime were weighed separately. Before weighing, all raw materials were crushed by a crusher until they all passed through a square-hole sieve with a aperture of 3.35 mm. The total sample weight for each scheme was 5 kg. The weighed raw materials were placed in a ball mill for mixing and grinding. The mixing and grinding process was carried out in the laboratory. The standard Bond index is performed in a ball mill.

[0062] The grinding process is as follows: 5 kg of weighed raw material is loaded into a ball mill equipped with steel ball media. The ball mill is started for grinding. The ball mill is stopped after every 50 revolutions. All the material is taken out, and the particle size distribution of the material is determined by standard sieve analysis. The sieve aperture size when 80% of the raw material passes through is calculated. At the same time, the fine powder under the sieve is weighed, and the amount of new fine powder generated per revolution of the ball mill is calculated. The sieve aperture size when 80% of the raw material passes through the mill is obtained through the particle size analysis of the mixture in advance.

[0063] Repeat the grinding-sieving cycle until the specific surface area of ​​the material reaches 320±10 m² / kg. Record the total number of revolutions of the ball mill when the target specific surface area is reached, and calculate the cumulative grinding energy consumption (i.e., unit energy consumption) based on the number of revolutions. Also calculate the grindability index of this group of raw material samples. In the formula, The abrasion index, This refers to the sieve aperture size that allows 80% of the ground product to pass through. The sieve aperture size is the size at which 80% of the feed material passes through the mill. To test the amount of newly generated fine powder produced per revolution of the ball mill, the grindability index was used. The smaller the value, the lower the energy consumption required to grind the raw materials to the same fineness, that is, the better the grindability of the raw materials, and the better the grinding economy of the corresponding coal slime to tailings replacement rate.

[0064] Bonder's index test was performed on all 11 groups of raw material samples. Each group of samples was tested in three parallel tests. The average value of the three grindability index measurements was taken as the final grindability index of the group. All test results were recorded to form a grindability index sequence data consisting of 11 grindability indices.

[0065] After completing the grindability test, the calcinability test of raw materials is carried out. Through high-temperature calcination test, the reactivity of raw materials with different proportions at high temperature is quantified, i.e., calcinability. The calcinability is evaluated by the free calcium oxide content in the clinker after calcination.

[0066] Eleven groups of raw material samples were prepared and thoroughly mixed. The samples were prepared by pressing. 100g of raw material sample was weighed, 5% distilled water was added, and the mixture was stirred evenly in a small mixer. The mixture was poured into a cylindrical mold with a diameter of 50mm and pressed for 1 minute under a pressure of 20MPa to make raw material cakes with a thickness of 10mm to 15mm. The prepared raw material cakes were placed in an electric heating drying oven and dried at 105±5℃ for 2 hours to remove free moisture.

[0067] The dried raw meal was placed in a high-temperature muffle furnace for calcination. In this embodiment, three different calcination temperatures were set: 1350℃, 1400℃, and 1450℃. The calcination process was as follows: the high-temperature muffle furnace was heated from room temperature to the set temperature at a rate of 10℃ / min. Once the furnace temperature reached the set temperature, the corundum crucible containing the raw meal was quickly pushed into the constant-temperature zone inside the furnace, and the timed constant-temperature calcination began. The constant-temperature calcination time was set to 30 minutes. After calcination, the crucible was quickly removed from the furnace and rapidly cooled using air cooling. Compressed air was used to purge the bottom of the crucible, allowing the clinker sample to cool from the calcination temperature to below 100℃ within 5 minutes to fix the mineral phase at high temperature.

[0068] The cooled clinker samples were crushed and ground until they passed through a square-hole sieve with a pore size of 0.08 mm to prepare analytical samples. The free calcium oxide content in each clinker sample was determined. Samples at each scheme and at each temperature were measured twice in parallel, and the arithmetic mean of the two measurements was taken as the final free calcium oxide content value.

[0069] All measured data were recorded. The burnability characteristic parameters included at least the free calcium oxide content values ​​at three different calcination temperatures. In this embodiment, the free calcium oxide content value of clinker measured at 1400℃ was used as the key burnability characteristic parameter for subsequent data linkage analysis. When the free calcium oxide content in the clinker was less than 1.5%, the clinker was considered to have qualified calcination quality and good burnability of the raw material.

[0070] After completing the grindability and burnability tests and obtaining all test data, a data linkage relationship was established and the optimal substitution rate window was determined. This was achieved by constructing a mathematical model that combined the obtained experimental data with process constraints to define the feasible range for replacing tailings with coal slime. The designed coal slime substitution rate for tailings was used as the independent variable, and the grindability index of the corresponding mix design and the free calcium oxide content of the clinker at 1400℃ calcination temperature were used as the dependent variables. Curve fitting was performed to construct the data linkage relationship. In this embodiment, the regression equation obtained through data fitting is: , In the formula, R is the replacement rate of coal slime with tailings. The predicted value of the wearability index as a function of R. The values ​​represent the predicted free calcium oxide content at a calcination temperature of 1400°C, as a function of R. is the fitting constant.

[0071] Based on the actual operation of the cement production line and the capacity of the grinding equipment, an upper limit critical value for the grindability index is set to ensure energy-efficient grinding. In this embodiment, the grindability index of the raw meal used for grinding is required to not exceed 13.5 kWh / ton. Simultaneously, based on clinker quality standards and subsequent cement performance requirements, an upper limit critical value is set to ensure the permissible free calcium oxide content of the clinker. In this embodiment, the free calcium oxide content of clinker calcined at 1400℃ is required to not exceed 1.5%.

[0072] Based on data linkage and constraint boundaries, the optimal substitution rate window is determined. The upper limit critical value of the grindability index and the upper limit critical value of the free calcium oxide content are substituted into the regression equation to solve for the substitution rate range that satisfies the grindability index of no more than 13.5 kWh / ton and the substitution rate range that satisfies the free calcium oxide content of no more than 1.5%. The overlapping interval of the two ranges is taken. This overlapping interval is the coal slime substitution rate interval that simultaneously satisfies the dual constraints of grinding economy and clinker burning quality. This interval is the optimal substitution rate window.

[0073] In a preferred embodiment, to comprehensively consider performance across multiple dimensions, a weighted comprehensive scoring method is used to determine the optimal substitution rate window, such as... Figure 2 As shown, it specifically includes:

[0074] The core evaluation indicators were determined, including the qualified rate of loss on ignition of clinker after calcination of each group of raw meal samples, the grindability index, and the free calcium oxide content of clinker at a calcination temperature of 1400℃.

[0075] The core evaluation indicators were subjected to dimensionless normalization. For the grindability index and free calcium oxide content, the smaller the value, the better the performance.

[0076] Based on the importance of the core evaluation indicators to the overall benefits of cement raw meal preparation and clinker calcination, the weighting coefficients for the loss on ignition qualification rate, grindability index, and free calcium oxide content are respectively assigned as α, β, and γ, respectively, satisfying α+β+γ=1. In this embodiment, ,according to Calculate the overall fitness score for each formulation, where, For the first The overall fitness score of the formulation scheme. , For the first The normalized value of the qualified rate of loss on ignition in the formulation scheme. For the first The normalized value of the grindability index of the formulation scheme. For the first The normalized value of the free calcium oxide content under the specified calcination temperature in the formulation scheme;

[0077] Calculate the overall fitness score for all options. Then, the coal slime replacement rate of tailings corresponding to the highest comprehensive fitness score is taken as the optimal matching center;

[0078] Expanding outwards from the optimal matching center, a comprehensive fitness score is formed. A continuous substitution rate range that is not lower than a preset threshold is the optimal substitution rate window. In this embodiment, the preset threshold is 0.85.

[0079] After determining the optimal substitution rate window, the best blending ratio of coal slime to tailings is finally determined. Within the optimal substitution rate window, the optimal blending ratio is finally determined by combining the stability of coal slime supply and the economic factors of batching.

[0080] The economic factors of the ingredients involve the unit cost accounting of all raw materials under each scheme. The raw materials include limestone, sandstone, iron powder, tailings and coal slime. After calculating the total unit raw material cost of all schemes, when the substitution rate is in the range of 55wt.% to 65wt.%, the total cost is the lowest and the economy is the best because the tailings cost is saved to the greatest extent and the amount of other corrective raw materials is not significantly increased.

[0081] Based on a comprehensive analysis of supply stability and economic efficiency, in this embodiment, the center value of the optimal substitution rate window is taken as the optimal blending ratio for coal slime to replace tailings. That is, the final selection of a coal slime substitution rate of 60 wt.% for tailings is the optimal blending ratio for industrial production.

[0082] To verify the optimal blending ratio determined by the method of this invention, a comparative experiment was conducted. The optimal blending ratio of coal slime to tailings determined by the method of this embodiment, i.e., 60 wt.%, was used for industrial-scale pilot production. This was compared with a control group that relied solely on chemical substitution, with the substitution rate of the control group set at 50 wt.%. The cement raw materials in both groups were ground in the same vertical mill system and calcined in the same rotary kiln under the same firing regime. The results of the comparative experiment are shown in Table 2.

[0083]

[0084] As shown in Table 2, the optimal blending ratio determined by the method of this invention, 60 wt.%, results in a raw meal grindability index of 12.9 kWh / ton, lower than the control group's 13.8 kWh / ton, indicating more energy-efficient grinding. The free calcium oxide content in the calcined clinker is 1.35%, lower than the control group's 1.82%, indicating better raw meal burnability and higher clinker quality. Furthermore, due to the zero-cost nature of coal slime, the cost per ton of raw meal is significantly reduced, achieving a dual optimization of economic efficiency and technical performance.

[0085] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A method for determining the compatibility of coal slime as a substitute for tailings coal through multi-gradient proportioning tests, characterized in that, The steps of this method are as follows: S100. Perform chemical composition analysis on the target coal slime sample and the reference tailings sample respectively, determine the main oxide content, moisture and received lower heating value of the target coal slime sample and the reference tailings sample respectively, and establish a basic chemical composition database of the target coal slime and a basic chemical composition database of the reference tailings. S200. Design N groups of multi-gradient proportioning schemes for replacing tailings with coal slime, including multiple experimental group schemes and blank control group schemes. By adjusting the amount of limestone, sandstone and iron powder raw materials, keep the target rate values ​​of lime saturation coefficient, silicon content and aluminum content of raw materials in the blank control group scheme and all experimental group schemes consistent with the target rate values ​​of the benchmark raw material proportioning scheme. S300. Prepare N groups of raw material samples, conduct a grindability test on each of the N groups of raw material samples, record the unit energy consumption required to grind each group of raw material samples to a preset surface area, calculate the grindability index corresponding to each group of raw material samples, and obtain a grindability index sequence data composed of N grindability indices. S400. Take raw material samples and, under the same working conditions, place each group of raw material samples at three different calcination temperatures for constant temperature calcination tests. Obtain the clinker samples corresponding to each group of raw material samples at each calcination temperature. Measure the free calcium oxide content of each clinker sample one by one and obtain the free calcium oxide content value corresponding to each group of raw material samples at the specified calcination temperature as a characteristic parameter of calcinability. S500: Construct a data linkage relationship between the coal slime replacement rate and the grindability index and the free calcium oxide content of clinker, respectively. Based on the upper limit critical value of the grindability index preset for cement production and the upper limit critical value of the free calcium oxide content that ensures the quality of clinker, determine the range of coal slime replacement rate for tailings that simultaneously meets the upper limit critical value of the grindability index and the upper limit critical value of the free calcium oxide content. S600. The range of coal slime to tailings replacement rate is taken as the optimal replacement rate window. Within the range of the optimal replacement rate window, an optimal ratio of coal slime to tailings is determined.

2. The method for determining the compatibility of coal slime as a substitute for tailings coal through multi-gradient proportioning tests according to claim 1, characterized in that, In the N groups of multi-gradient ratio schemes for replacing tailings with coal slime, the first group is a blank control group scheme with a coal slime replacement rate of 0 wt.% for tailings, and the second to Nth groups are experimental groups. The coal slime replacement rate for tailings in the second to Nth groups increases in a mass percentage gradient until the coal slime replacement rate for tailings in the Nth group reaches 100 wt.%.

3. The method for determining the compatibility of coal slime as a substitute for tailings coal through multi-gradient proportioning tests according to claim 1, characterized in that, In the S300 process, the grindability test is conducted using the Bonder's index method, with each group of raw material samples ground until the specific surface area reaches 320±10m². 2 The grinding efficiency index corresponding to / kg is used as the grinding efficiency index. ,in, The grindability index, i.e., energy consumption per unit, This refers to the sieve aperture size that allows 80% of the ground product to pass through. The sieve aperture size is the size at which 80% of the feed material passes through the mill. To test the amount of new fine powder generated per revolution of the small mill.

4. The method for determining the compatibility of coal slime as a substitute for tailings coal through multi-gradient proportioning tests according to claim 1, characterized in that, In the S400, there are three different calcination temperatures: 1350℃, 1400℃, and 1450℃, with the specified calcination temperature being 1400℃.

5. The method for determining the compatibility of coal slime as a substitute for tailings coal through multi-gradient proportioning tests according to claim 1, characterized in that, The specific steps of S500 are as follows: The core evaluation indicators were determined, including the qualified rate of loss on ignition of clinker after calcination of each group of raw meal samples, the grindability index, and the free calcium oxide content of clinker at a specified calcination temperature. The core evaluation indicators are subjected to dimensionless normalization, and the original values ​​of each core evaluation indicator are uniformly mapped to dimensionless values ​​in the interval [0, 1]. Based on the importance of the core evaluation indicators to the overall benefits of cement raw meal preparation and clinker calcination, weighting coefficients are assigned to the loss on ignition qualification rate, grindability index, and free calcium oxide content, respectively. , , γ, and satisfy ; according to Calculate the overall fitness score for each formulation. ,in, For the first The overall fitness score of the formulation scheme. , For the first The normalized value of the qualified rate of loss on ignition in the formulation scheme. For the first The normalized value of the grindability index of the formulation scheme. For the first The normalized value of the free calcium oxide content under the specified calcination temperature in the formulation scheme; Comprehensive fitness score The coal slime replacement rate of tailings corresponding to the highest value is taken as the optimal compatibility center. A comprehensive fitness score is formed by expanding outwards from the optimal compatibility center. A continuous substitution rate range that is not lower than a preset threshold is used as the optimal substitution rate window.

6. The method for determining the compatibility of coal slime as a substitute for tailings coal through multi-gradient proportioning tests according to claim 1, characterized in that, In S200, the lime saturation coefficient value The allowable deviation range is ±0.01, silicon ratio value The allowable deviation range is ±0.05, aluminum ratio value The permissible deviation range is ±0.05; The lime saturation coefficient value The silicon ratio value The aluminum ratio value Among them, CaO, , , These represent the mass percentage of the corresponding oxides in the raw meal.

7. The method for determining the compatibility of coal slime as a substitute for tailings coal through multi-gradient proportioning tests according to claim 1, characterized in that, In S100, the main oxide contents determined by chemical composition analysis of the target coal slime sample and the reference tailings sample include the mass percentage of loss on ignition, silicon dioxide, aluminum oxide, ferric oxide, calcium oxide, and magnesium oxide.

8. The method for determining the compatibility of coal slime as a substitute for tailings coal through multi-gradient proportioning tests according to claim 1, characterized in that, In the constant temperature calcination test of S400, the constant temperature calcination time at each calcination temperature is 30min-60min. The rapid cooling adopts air cooling or water cooling to cool the calcined clinker sample from the calcination temperature to <100℃ within 5min.

9. The method for determining the compatibility of coal slime as a substitute for tailings coal through multi-gradient proportioning tests according to claim 1, characterized in that, In S600, the center value of the optimal substitution rate window is taken as the optimal blending ratio of coal slime to tailings.